Sepsis-Induced Diabetic Ketoacidosis (DKA) in Latent Autoimmune Diabetes in Adult (LADA) - Fadel Fikri Suharto; Alwi Shahab; Yulianto Kusnadi; RM Dewi Anggraini (HM Publisher, 2022)
Backgrounds. Latent autoimmune diabetes in adults (LADA) is a slowly progressive form of autoimmune diabetes mellitus characterized by older age at diagnosis, presence of pancreatic autoantibodies, and lack of absolute insulin requirement at diagnosis. Patients with LADA had better β-cell function than patients with classic Type 1 DM (T1DM). Overtime, LADA tends to experience rapid and progressive loss of beta cell function that requires intensive insulin therapy. This case report aims to describe a case of Diabetic Ketoacidosis (DKA) in a patient with latent autoimmune diabetes in adult (LADA) induced by sepsis (urinary tract infection/UTI). Case Presentations. A woman, 28 years-old, came to the Emergency Department (ED) RSMH Palembang with chief complaints of decreased consciousness and shortness of breath. Patient had a history of frequent urination, pain when urinating, and fever. Urinalysis examination were glycosuria, proteinuria, hematuria. Hb-A1c level was 10.7%, C-Peptide 0.11 ng/dL, Anti GAD65 qualitative positive, and Islet cell antibody (ICA) negative. Patient was diagnosed with diabetic ketoacidosis (DKA), LADA, and sepsis due to urinary tract infection (UTI). Patients were managed with DKA and sepsis management algorithm. Conclusion. Diabetic ketoacidosis (DKA) in LADA caused by sepsis is an emergency in the metabolic endocrine and diabetes fields. Prompt and appropriate management can improve outcome prognosis in this case.